A Thalamic-Fronto-Parietal Structural Covariance Network Emerging in the Course of Recovery from Hand Paresis after Ischemic Stroke - Abela, Eugenio; Missimer, John H.; Federspiel, Andrea; Seiler, Andrea; Hess, Christian Walter; Sturzenegger, Matthias; Wiest, Roland; Weder, Bruno J. (Frontiers in Neurology, 2015)
Aim: To describe structural covariance networks of grey matter volume (GMV) change in 28 patients with first-ever stroke to the primary sensorimotor cortices, and to investigate their relationship to hand function recovery and local GMV change. Methods: Tensor based morphometry maps derived from high resolution structural images were subject to principal component analyses to identify the networks. We calculated correlations between network expression and local GMV change, sensorimotor hand function and lesion volume. To verify which of the structural covariance networks of GMV change have a significant relationship to hand function we performed an additional multivariate regression approach. Results: Expression of the second network, explaining 9.1% of variance, correlated with GMV increase in the medio-dorsal (md) thalamus and hand motor skill. Patients with positive expression coefficients were distinguished by significantly higher GMV-increase of this structure during stroke recovery. Significant nodes of this network were located in md thalamus, dorsolateral prefrontal cortex and higher order sensorimotor cortices. Parameter of hand function had a unique relationship to the network and depended on an interaction between network expression and lesion volume. Inversely network expression is limited in patients with large lesion volumes. Conclusions: Chronic phase of sensorimotor cortical stroke has been characterized by a large scale covarying structural network in the ipsilesional hemisphere associated specifically with sensorimotor hand skill. Its expression is related to GMV-increase of md thalamus, one constituent of the network, and correlated with the cortico-striato-thalamic loop involved in control of motor execution and higher order sensorimotor cortices. A close relation between expression of this network with degree of recovery might indicate reduced compensatory resources in the impaired subgroup.